MENINGKATKAN MINAT LITERASI PADA SISWA MELALUI MEMBACA, VIDEO DAN GAME PADA SISWA KELAS 10 DI MAN INSAN CENDEKIA KOTA PALU - Anggreni, Afrillia; Zamzam, Fadhilah; Rosmah, Mardiati; Rachman, Januar; Rizkoh, Fusthaatul; Aini, Putri Nur; Ningsih, Novi Sulistya; Rahm, Aulia; Maryam, Maryam (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
The Literacy Programme is an innovative initiative designed to increase the mastery of reading interest in students at MAN Insan Cendekia Kota Palu. This programme is implemented by students who are members of the Merdeka Belajar Kampus Merdeka (MBKM) programme with the aim of creating a fun and interactive learning environment. Through various activities such as reading stories, watching videos, and charades, students are given the opportunity to learn English in a more natural and fun way.This study aims to evaluate the effectiveness of the Literacy programme in improving the mastery of reading interest in students at MAN Insan Cendekia Kota Palu. The results obtained showed that the approach implemented was able to increase students' interest and motivation in Literacy specifically reading in English, which led to a significant increase in their vocabulary mastery. The programme not only enriched students' knowledge, but also built their confidence in using English in daily life. This innovation and creative approach to learning is expected to be a model for other schools in their efforts to improve students' English competence.